SHAPING OF NOVA SHELLS - THE CASE OF NOVA V 1974 CYGNI - Chochol, D.; Pribulla, T. (Одеські астрономічні публікації, 2017)
Expanding shell of Nova V 1974 Cygni consists of two major components: an outer fast - low-mass envelope and an inner slow high-mass envelope. The outer envelope, detected in diffuse enhanced spectra and on radio images, is shaped and accelerated by the fast wind consisting of spherical and polar components. The inner envelope, detected in nebular spectra and on the HST images, consists of equatorial ring and polar blobs. Common envelope phase and strong magnetic field of the O-Ne-Mg white dwarf play an important role in shaping of the inner envelope. Both envelopes are prolate.